Characterization of different substrates for Raman spectroscopic imaging of eukaryotic cells. (2nd March 2016) - Ramoji, Anuradha; Galler, Kerstin; Glaser, Uwe; Henkel, Thomas; Mayer, Günter; Dellith, Jan; Bauer, Michael; Popp, Jürgen; Neugebauer, Ute
Abstract : For Raman spectroscopic analyses of the cells and other biological samples, the choice of the right substrate material is very important to avoid loss of information in characteristic spectral features because of competing background signals. In the current study, Raman spectroscopy is used to characterize several potential Raman substrates. Raman vibrational bands of the substrate material are discussed. The surface topography is analyzed by atomic force microscopy, and the root mean square surface roughness values are reported. Biocompatibility of the substrates is tested with Hep G2 cells evaluating cellular morphology as well as live/dead staining. Calcium fluoride, silicon, fused silica, borofloat glass, and silicon nitride membranes support cell growth and adherence. Silicon, borofloat glass, and fused silica give rise to Raman signals in the region of interest. Calcium fluoride substrate (UV grade) is suitable for Raman spectroscopic investigation of living cells. Nickel foil is suitable substrate for Raman spectroscopic investigation but cellular adherence and viability depend on the quality of the foil. Silicon nitride membranes coated with nickel chrome is a suitable Raman substrate in closed microfluidic systems. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Different materials are characterized for their suitability as substrates for Raman measurement of biological cells assessing their surface roughness, background Raman signal and biocompatibility.